The patterns and changes of general surgical presentations during the first wave COVID-19 pandemic at a metropolitan Sydney hospital - Diab, Jason; Nguyen, Quoc Dung; Khaicy, David; Diab, Vanessa; Hopkins, Zachias; Badiani, Sarit; Berney, Christophe (International Surgery Journal, 2022)
Background: The impact of SARS-COV-2 virus (COVID-19) has been well documented in international settings with a reduction in overall emergency presentations both influenced by social distancing and lockdowns. This study focuses on several common acute general surgical pathologies exploring differences in presentations and clinical outcomes for appendicitis, cholecystitis, and incarcerated hernias during the first wave. Methods: A retrospective review of medical records of all patients was analysed in two groups: the non-COVID-19 group (combined 2017-2019) and the COVID-19 group (2020). Results: There were 3,316 acute emergency surgical presentations with an 8.2% decrease in total presentations in 2020. There were 477 appendicectomies, 224 cholecystectomies, and 121 repair of incarcerated hernias. All general surgical procedures demonstrated significant differences between non-COVID and COVID cohorts, including length of stay (LoS) (2.7 vs. 2.1, p=0.009) and onset of symptoms (1.6 vs. 2.2, p=0.018) for those aged less than 25 years. Patients with appendicitis aged less than 25 years had a significantly longer onset of symptoms before hospital presentation and shorter LoS in the COVID group (1.7 vs. 2.5, p=0.002; 2.9 vs. 2.3, p=0.016). Likewise, patients with cholecystitis had a significantly longer onset of symptoms in the COVID-19 cohort compared to their counterparts (2.0 vs. 3.0 days, p=0.025). There were no significant differences in biochemical, clinical or post-operative outcomes. Conclusions: The first wave of the COVID-19 pandemic significantly reduced acute general surgical presentations. For those less than 25 years in the COVID-19 cohort, overall LoS was shorter despite indicating significantly delayed presentations.